MANAJEMEN KEPALA SEKOLAH DALAM PEMBINAAN KOMPETENSI GURU DI SEKOLAH MENENGAH PERTAMA (SMP) NAMIRA MEDAN - Arafit Hasan Fachruddin Azmi, Syaukani (Pascasarjana UIN Sumatera Utara, 2017)
Abstract: This study aims to identify and analyze the implementation pattern Management in Improving Teacher Competence Junior High School (SMP) Namira Medan, which includes planning, organizing, actuating, evaluation and controlling. In analyzing the data the researchers used qualitative analysis techniques to the process of data reduction, exposure data and drawing conclusions. There were four findings in this study, namely: 1) planned teacher competency development activities to be carried out by school teachers in the period (a period of) specific. 2) organizing by dividing tasks according to their ability and professionalism. 3) actuating influential in improving the quality of teaching and learning, this is due to the mechanism more effective and faster to take advantage of school resources based on need. 4) Approaches were made by way of familiarizing themselves with the teacher. a visit to the teachers lounge. From the interviews that researchers do indicate that the principal establish good relations with teachers and employees in junior Namira stat Medan.Penelitian ini bertujuan untuk mengetahui dan menganalisis implementasi Manajemen Kepala Sekolah dalam Pembinaan Kompetensi Guru Sekolah Menengah Pertama (SMP) Namira Medan, yang meliputi Perencanaan, pengorganisasian, pelaksanaan pembinaan, dan pengawasan terhadap Kompetensi guru. Dalam menganalisis data peneliti menggunakan teknik analisis kualitatif dengan proses reduksi data, pemaparan data dan penarikan kesimpulan. Ada empat temuan dalam penelitian ini, 1) perencanaan program-program pembinaan kompetensi guru adalah rencana kegiatan pembinaan kompetensi guru yang akan dilaksanakan oleh guru sekolah dalam kurun waktu satu periode. 2) pengorganisasian dengan membagi tugas sesuai dengan kemampuan dan profesionalitas. 3) pelaksanaan peningkatan kualitas belajar mengajar, hal ini disebabkan adanya mekanisme yang lebih efektif. 4) pengawasan dan evaluasi dilakukan dengan mendorong guru untuk kreatif dan inovatif dengan melakukan beberapa pendekatan terhadap guru-guru.Kata Kunci: Manajemen, Kepala Sekolah, Kompetensi Guru.